The free groin flap in the rat: a model for improving microsurgical skills and for microvascular perfusion studies. Issue 3 (June 2014) - Wallmichrath, Jens; Baumeister, R. G. H.; Gottschalk, O.; Giunta, R. E.; Frick, A.
Abstract: The goal of this study was to evaluate the free groin flap in the rat transplanted to the neck as a tool for extending microsurgical skills and to assess its suitability as a model for microvascular perfusion studies following secondary venous ischaemia. An analysis of 60 consecutive groin flap transplantations was performed in male Sprague Dawley rats with special regard to anatomy and operation times (Part I, animals No. 1–60). Following flap transplantation, the animals No. 10–30 ( n = 21) were used for the determination of the critical time period of a complete venous stasis of the free groin flap resulting in a total flap loss (Part II). The flaps of animals No. 31–41 ( n = 11) were used for assessing the feasibility and reproducibility of intra-vital video microscopy (IVM) of the flaps (Part III). The mean total operation time decreased from 166 (± 26) minutes ins the first 10 animals to 126 (± 21) minutes and 130 (± 12) minutes in the latter two groups of 10 animals, respectively. After a critical period of 35 minutes of a complete artificial venous stasis a complete flap necrosis occurred. IVM detected a higher functional capillary density of the skin of the transplanted groin flaps in the animals in which the flaps were rinsed with 1 ml of Ringer's lactated solution prior to I/R. In conclusion, this model is simple and reliable. The model may be a useful tool for evaluating and comparing the effects of various anticoagulants or vasomotor drugss on microvascular perfusion in critically compromised free flaps.